2013
DOI: 10.1016/j.jor.2013.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Elastic Stable Intramedullary Nailing for treating paediatric long bone fractures

Abstract: This study reports the complications observed in children with long bone fractures treated using Elastic Stable Intramedullary Nailing (ESIN). One hundred and sixty-four (n = 164) fractures in 160 patients under the age of 16 years formed the basis of our review. This included 108 boys and 52 girls with the median age of 11 years and median follow up of 7.5 months. The analysis included fractures of the radius/ulna, humerus, femur and tibia. All pathological fractures were excluded. In this series 54 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 35 publications
0
22
1
Order By: Relevance
“…Although being rare when appropriate technique is used, some weaknesses have been reported in ESIN 13,15,21,22 . A metallic implant predisposes the patient to bacterial infections, may cause local pain and soft-tissue irritation [23][24][25][26] and may interfere with radiological imaging. Radial nerve lesion, delayed union, nonunion, re-fracture 27 and compartment syndrome may occur 5,10,19,21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Although being rare when appropriate technique is used, some weaknesses have been reported in ESIN 13,15,21,22 . A metallic implant predisposes the patient to bacterial infections, may cause local pain and soft-tissue irritation [23][24][25][26] and may interfere with radiological imaging. Radial nerve lesion, delayed union, nonunion, re-fracture 27 and compartment syndrome may occur 5,10,19,21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Of the excluded full texts, the most common reason for exclusion was that open fractures could not be separated (10 studies) [19][20][21][22][23][24][25][26][27][28] followed by studies with too small population (7 studies). [29][30][31][32][33][34][35] In two studies, 36,37 distal tibia fractures were no distinguishable from diaphyseal fractures, and two studies 38,39 reported only the incidence of compartment syndrome. Three additional studies reporting only epidemiological data, 40 surgical technique, 41 and long-term outcomes, 42 respectively, were excluded.…”
Section: Resultsmentioning
confidence: 99%
“… 21 Soft-tissue irritation has been reported as a complication of FNs in multiple studies, with incidence ranging from < 10% to as high as 52% 22 but is minor in most cases and relieved with implant removal. 8 , 21 , 23 – 25 Proposed risk factors for irritation include bent or prominent nail ends, 22 earlier mobilization of the knee 12 and excessive nail protrusion at the time of implantation. Accordingly, studies have advocated immobilization, 23 leaving < 2.5 cm of nail protrusion, and minimizing bending the ends of the nails outside the bony cortex during insertion and trimming of the nails to help decrease soft-tissue irritation.…”
Section: Discussionmentioning
confidence: 99%